Impact of interchange fees rates on the Polish payment cards market - Maciejewski, Krzysztof (Copernican Journal of Finance & Accounting, 2013)
The aim of this paper is to indicate the importance of the interchange fee on the payment card market in Poland and its impact on the development of the acceptance network. The paper uses a descriptive and comparative analysis, as well as results of analyses and research, including a survey conducted by the author among seven acquirers. Of key importance for the development of payment card acceptance network are costs of payment card acceptance. One of the main components of Merchant Service Charge is interchange fee. The level of interchange fees rates in Poland, being one of the highest in the EU, is a major barrier to the development of payment card acceptance network and cashless transactions. The central bank was engaged in the process of interchange fees reduction in Poland, assuming the role of a catalyst. The reduction of interchange fees (since 2013) in the Polish market is a positive development which may result among others in implementation of costly efficient mobile payment systems.